Nitrogen fertilizer replacement value of black soldier fly frass fertilizer and synchrony of nitrogen mineralization for maize production - Beesigamukama, Dennis; Mochoge, Benson; Korir, Nicholas Kibet; Musyoka, Martha W; Fiaboe, Komi K M; Nakimbugwe, Dorothy; Khamis, Fathiya Mbarak; Subramanian, Sevgan; Dubois, Thomas; Ekesi, Sunday; Tanga, Chrysantus M (PANGAEA, 2020)
Though, the use of black soldier fly frass fertilizer (BSFFF) is promoted globally, information on nitrogen (N) fertilizer replacement value (NRFV) and synchrony of N mineralization for crop production remains largely unknown. Comparative studies between BSFFF and commercial organic fertilizer (SAFI) were undertaken under field conditions to determine synchrony of N release for maize uptake. The BSFFF, SAFI and urea fertilizers were applied at the rates of 0, 30, 60 and 100 kg N ha-1. Yield data from urea treated plots were used to determine the NFRV of both organic inputs. Results showed that maize from BSFFF treated plots had higher N uptake than SAFI treated plots. High N immobilization was observed throughout the active growth stages of maize in soil amended with BSFFF while soil treated with SAFI achieved net N release at the silking stage. Up to 3 times higher negative N fluxes were observed in SAFI amended soils compared to BSFFF treated plots at tasseling stage. The BSFFF applied at 30 and 60 kg N ha-1 achieved significantly higher NFRV than all SAFI treatments. Our findings revealed that BSFFF is a promising and sustainable alternative to SAFI and/or Urea for enhanced maize production.
Keywords: Frass fertilizer; Hermertia illucens; maize; Nitrogen fertilizer replacement value; Nitrogen mineralization; Nitrogen synchrony